Світовий досвід надання психологічноії допомоги вагітним жінкам - Малєєва, К. А.; Malieieva, K. A. (Габітус. - 2022. - Вип. 41. - С. 290-294, 2022)
Проведено теоретичний аналіз наукових праць у сфері перинатальної психологічної допомоги вагітним різних країн світу. Визначено основні напрями психологічної допомоги вагітним – психопрофілактичний та психокорекційний. Наведено огляд сучасних державних програм підготовки до пологів у різних країнах світу, в тому числі – в Україні. Висвітлено основні психологічні проблеми вагітних жінок та шляхи і засоби їх вирішення за допомогою психокорекційного втручання. Показано, що основними психопрофілактичними завданнями допологової підготовки є психологічна підготовка жінок до вагітності, пологів, формування позитивного ставлення жінки до майбутньої дитини та пологів, підготовка партнера або членів родини до участі у пологах, усвідомлення своєї ролі в процесі вагітності та пологів.

The statistics present an overview of the world experience of providing psychological care assistance to pregnant women. A theoretical analysis of scientific works was carried out in the field of perinatal psychological care for pregnant women in different countries of the world. The main directions of direct psychological help are defined: psychoprophylactic and psychocorrective. An overview of modern stable program of preparation for childbirth in different countries of the world, and the main number is in Ukraine. The main psychological problems of pregnant women and ways are revealed and means of solving them with the help of psychocorrective intervention. It is shown that the main psychoprophylactic tasks of prenatal care preparation is the psychological preparation of women for pregnancy, childbirth, the formation of a positive attitude of a woman to the future child and childbirth, preparing a partner or family member to participate in childbirth, getting to know one’s family ties roles in the processes of pregnancy and childbirth. The Ministry of Health of Ukraine recommends paying to solving these tasks by specialists such as obstetrician-gynecologists, midwives, neonatologists, psychologists. Most often psychological prenatal training of pregnant women in rich countries of the suite is carried out by midwives. The problem of lack of missing roles of perinatal psychologists is raised prenatal preparation will prepare pregnant women as needed by his decision at the expense differentiation of the spheres of broad psychology in specialized medical and social attitudes. The analysis of foreign scientific literature made it possible to establish the main psychological problems faced by pregnant women (depression, anxiety, perinatal loss, etc.). Foreign scientific works are also devoted to the analysis of the results of work with injuries suffered by pregnant women, to the study of the impact of negative experiences of violence, smoking, miscarriages, etc. The main ones the trends of such works are related to the search for adequate and effective ones technologies of psychotherapeutic intervention aimed at recovery mentally healthy pregnant women.

Проведен теоретический анализ научных работ в сфере перинатальной психологической помощи беременным разных стран мира. Определены основные направления психологической помощи беременным – психопрофилактическое и психокоррекционное. Представлен обзор современных государственных программ подготовки к родам в разных странах мира, в том числе – в Украине. Отражены основные психологические проблемы беременных женщин и пути и средства их решения с помощью психокоррекционного вмешательства. Показано, что основными психопрофилактическими задачами дородовой подготовки является психологическая подготовка женщин к беременности, родам, формирование положительного отношения женщины к будущему ребенку и родам, подготовка партнера или членов семьи к участию в родах, осознание своей роли в процессе беременности и родов.
Global experience of providing psychological assistance to pregnant women
Малєєва, К. А. Світовий досвід надання психологічноії допомоги вагітним жінкам / Малєєва К. А. // Габітус. - 2022. - Вип. 41. - С. 290-294. - DOI: https://doi.org/10.32782/2663-5208. 2022.41.51.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; перинатальна психологія; perinatal psychology; перинатальная психология; психологічна допомога; psychological help; психологическая помощь; вагітні жінки; pregnant women; беременные женщины